Delayed neurological sequelae of carbon monoxide poisoning: a case report - Sah, Sunny Kumar; Regmi, Shaswat (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Delayed neurological sequelae of Carbon Monoxide poisoning is commonest neurological complication of CO poisoning. Presentation can be confusing with other differentials like stroke and delayed neuropathy of OP poisoning. Imaging like MRI head can be helpful for diagnosis. Different predicting tools are available for the development of DNS. Early detection and prompt management of CO poisoning with normobaric oxygen can prevent DNS. Some conditions requires Hyperbaric oxygen too.